Analisis Content Marketing terhadap Brand Awareness melalui Customer Engagement pada Instagram Reels Discovery Kartika Plaza Hotel Bali - I Made Adrian Wiguna; Kadek Cahya Dewi; Laily Fauziah (Trending: Jurnal Manajemen dan Ekonomi, 2026)
The increasingly intense competition in the hospitality industry requires companies to effectively utilize social media to build brand awareness. However, challenges remain in creating content that can enhance audience engagement and strengthen brand awareness. This study aims to analyze the effect of content marketing on brand awareness through customer engagement as a mediating variable on Discovery Kartika Plaza Hotel Bali’s Instagram Reels. This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 170 respondents who were active Instagram users and had viewed Discovery Kartika Plaza Hotel Bali’s Instagram Reels content. The sampling technique used was purposive sampling with a non-probability sampling approach. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The results indicate that content marketing has a positive and significant effect on customer engagement. Customer engagement also has a positive and significant effect on brand awareness. In addition, content marketing has a positive and significant effect on brand awareness, both directly and indirectly through customer engagement as a mediating variable. These findings suggest that attractive, relevant, and consistent content can enhance audience engagement, thereby strengthening brand awareness. Therefore, content marketing strategies through Instagram Reels can serve as an effective means of increasing the brand awareness of Discovery Kartika Plaza Hotel Bali.